Transition-metal-free radical approach for the synthesis of isothiocyanates by pyridinium 1,4-zwitterionic thiolates as a sulfur source - Mobarakeh, Fatemeh Abdiyan; Khosravi, Hormoz; Akbari, Alireza; Rominger, Frank; Balalaie, Saeed (The journal of organic chemistry, 2025)
Herein, we disclose a novel, mild, transition-metal-free approach to synthesizing diversely functionalized isothiocyanates from the corresponding isocyanide precursors, achieving high to excellent yields (up to 97%). The current method sheds light on the reactivity of pyridinium 1,4-zwitterionic thiolates as an unprecedented sulfur source strikingly distinct from their previously known reactivity in ionic annulation reactions, showcasing an innovative approach to organic synthesis.